2021
DOI: 10.2174/0929866527666200617124221
|View full text |Cite
|
Sign up to set email alerts
|

Bifunctional Inhibitors from Capsicum chinense Seeds with Antimicrobial Activity and Specific Mechanism of Action Against Phytopathogenic Fungi

Abstract: Background: Antimicrobial peptides (AMPs) are found in the defense system in virtually all life forms, being present in many, if not all, plant species. Objective: The present work evaluated the antimicrobial, enzymatic activity and mechanism of action of the PEF2 fraction from Capsicum chinense Jack. seeds against phytopathogenic fungi. Methods: Peptides were extracted from C. chinense seeds and subjected to reverse-phase chromatography on an HPLC system using a C18 column coupled to a C8 guard column, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 48 publications
0
6
0
Order By: Relevance
“…Other works have already demonstrated the presence of different peptides with antimicrobial activity in Capsicum seeds, but these peptides have been isolated through methodologies other than chitin affinity columns. [27,39,45,46] Therefore, this is the first work that uses a chitin column to obtain peptide-rich fractions with antimicrobial activity from the seeds of the Capsicum genus. In other plant species, low molecular weight proteins have been purified using a chitin affinity column.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other works have already demonstrated the presence of different peptides with antimicrobial activity in Capsicum seeds, but these peptides have been isolated through methodologies other than chitin affinity columns. [27,39,45,46] Therefore, this is the first work that uses a chitin column to obtain peptide-rich fractions with antimicrobial activity from the seeds of the Capsicum genus. In other plant species, low molecular weight proteins have been purified using a chitin affinity column.…”
Section: Discussionmentioning
confidence: 99%
“…[23] In recent years, within our group, several Capsicum peptides have already been isolated and characterized, such as thionine-like, [24] defensin, [25] lipid transport proteins (LTPs) [26] and proteinase inhibitors. [27] In this study, for the first time, we used a chitin-binding column to purify peptiderich fractions from seeds of C.annuum with chitin-binding activity and antimicrobial activity against yeasts.…”
Section: Introductionmentioning
confidence: 99%
“…Antimicrobial peptides extracted from different plant organs, such as seeds and fruits of the genus Capsicum, have already been described and characterized previously [13,15,[23][24][25][26][27]. Silva and coauthors (2014) [12], showed the antimicrobial potential of protein fractions obtained from seeds of C. chinense Jacq. accession UENF 1755 on the fungi Colletotrichum gloeosporioides, C. lindemunthianum, Fusarium oxysporum and F. solani, in addition to the inhibition of the activity of trypsin and α-amylase enzymes.…”
Section: Extraction and Characterization Of Peptides From Immature An...mentioning
confidence: 99%
“…In plants of the genus Capsicum, peptides characterized as inhibitors of trypsin and chymotrypsin-protease with antifungal activity (MIC 50-250 μg.mL -1 ) were identified, mainly in C. annuum and C. chinense [10,11]. The antifungal activity of these AMPs was characterized by visualization of cell agglomeration and pseudohyphae formation or by hyphal morphological changes as well as by membrane permeabilization due to reactive oxygen species (ROS) induction [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, desalination (low-pressure chromatography) has emerged as an alternative to dialysis. This technique involves the use of hydrophobic adsorbents, such as phenyl-agarose, reverse phase C8, and C18 [ [107] , [108] , [109] ]. RP-HPLC has become a primary purification method for peptides and other small compounds due to its good selectivity and high separation performance.…”
Section: Application Of Ms In Amps Studymentioning
confidence: 99%